Rebolusyong Pilipino : tanaw mula sa loob - Sison, Jose Maria, 1939- (Lunsod ng Quezon, Pilipinas : Lagda Pub., 1994)
Questions and answers on political condition in the Philippines.
In Tagalog.
Keywords: Philippines -- Politics and government -- 1946-